Your Sacred Self : Making the Decision to be Free - Dyer, Wayne W. (New York An Imprint of HarperCollins Publishers, 2001)
Revealing a three-step program to help readers understand their place in the world and develop a sense of satisfaction with themselves and others, this book is liberating and enriching. Dyer teaches readers how to tap into the power of their higher selves and live each day with a greater sense of peace and fulfillment. National ads/media.
Include Index
Keywords: Self-actualization (Psychology) -- Spiritual life